2000
DOI: 10.1021/jp000801o
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Pt(II) by H2:  Effects of Citrate and NaOH and Reaction Mechanism

Abstract: Aqueous solutions of Pt(II) (aged PtCl4 2- solutions) are reduced by hydrogen in the absence of a stabilizer and in the presence of stabilizing sodium citrate or/and sodium hydroxide. The rate of reduction is measured optically and conductometrically, and the colloidal nanoparticles, which are finally formed, are studied by high-resolution electron microscopy. In dilute solutions, the rate of reduction is proportional to the square of the Pt(II) concentration. In the presence of citrate and NaOH, the reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
120
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(126 citation statements)
references
References 14 publications
6
120
0
Order By: Relevance
“…The use of a strong reducing agent, such as NaBH 4 , results in tiny particles that are well dispersed. 29 Nowadays, a succession of chemical reductants can been used for the synthesis of noble metal nanoparticles which contain NaBH 4 35 formaldehyde, 36 formamide, 37 Tollens' reagents, 38 ethylene glycol, 39 ethanol, 40 citrate, 32,40 aniline, 41 polyaniline, 42 or ascorbic acid. 43 Layered silicates, eg, montmorillonite (MMT), have been used in polymer nanocomposites with a significant improvement in mechanical properties.…”
mentioning
confidence: 99%
“…The use of a strong reducing agent, such as NaBH 4 , results in tiny particles that are well dispersed. 29 Nowadays, a succession of chemical reductants can been used for the synthesis of noble metal nanoparticles which contain NaBH 4 35 formaldehyde, 36 formamide, 37 Tollens' reagents, 38 ethylene glycol, 39 ethanol, 40 citrate, 32,40 aniline, 41 polyaniline, 42 or ascorbic acid. 43 Layered silicates, eg, montmorillonite (MMT), have been used in polymer nanocomposites with a significant improvement in mechanical properties.…”
mentioning
confidence: 99%
“…CTAB probably forms micellar species since its concentration in solution (around 5 mM in the final solution) is higher than the Critical Micellar Concentration (0.8-1.1 mM) [37]. When the aged H 2 PtCl 6 solution is added, the Pt 4+ cation could be surrounded by different coordination shells since the ageing of the solution is supposed to lead to the partial or complete substitution of chloride ligands by hydroxides ones [21,22,38]: (1), an interaction between CTAB and the platinate salt could be envisaged. Such an interaction could lead to {Pt 4+ -CTAB} moieties as it was previously demonstrated for palladium [14].…”
Section: Proposition Of a Mechanism For Platinum Nanoparticles Formationmentioning
confidence: 99%
“…Tetrahedra were also obtained using polyvinylpyrrolydone (PVP), adjusting the pH permitted to form up to 75% of tetrahedra [19,20]. Platinum nanoparticules with well defined morphologies were obtained using citrate as a structure directing agent [21,22]. So, without or with low amounts of citrate, cubes and truncated octahedra were observed and when the proportion of citrate was raised, the proportion of tetrahedra was increased.…”
Section: Introductionmentioning
confidence: 99%
“…139 They conclude that the electrode has a larger influence on smaller Au NPs due to more points of interaction. This work is relevant to the early findings where small metal clusters showed a positive shift in oxidation potential 112,127 instead of the predicted negative shift and is similar to the phenomenon of underpotential deposition. 140 More recently, Kuo and Hwang showed by voltammetry that the oxidation potential of Ag NPs depends on the shape and follows the order of cubes > spheres > decahedrons > triangular plates.…”
Section: Introductionmentioning
confidence: 56%
“…Previously, Henglein and Giersig showed that the reduction of PtCl4 2-occurs more slowly in the presence of citrate and NaOH. 127 It is well-known that pH plays a role in the synthesis of citrate-coated metal NPs. Peng and coworkers described the influence of pH on the size/shape distribution and the size/shape evolution of Au NPs.…”
Section: Introductionmentioning
confidence: 99%